2021
DOI: 10.2196/28242
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Mobile Telerehabilitation Solution on Metabolic Health Outcomes and Rehabilitation Adherence in Patients With Obesity: Randomized Controlled Trial

Abstract: Background Obesity is a major public health issue. Combining exercise training, nutrition, and therapeutic education in metabolic rehabilitation (MR) is recommended for obesity management. However, evidence from randomized controlled studies is lacking. In addition, MR is associated with poor patient adherence. Mobile health devices improve access to MR components. Objective The aim of this study is to compare the changes in body composition, anthropome… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 66 publications
(70 reference statements)
1
8
0
Order By: Relevance
“…Follow-up of a cohort of 12 obese patients regularly followed over 96 months (results partially presented in [33] and further updated in January 2022). This is the continuation of previously presented shorter follow-up studies [17,18,231,256]. Results show that the weight-lowering effect of LIPOXmax training persists over more than 8 years.…”
Section: Effects Of Lipoxmax Training On Obesity and Associated Disor...supporting
confidence: 84%
See 1 more Smart Citation
“…Follow-up of a cohort of 12 obese patients regularly followed over 96 months (results partially presented in [33] and further updated in January 2022). This is the continuation of previously presented shorter follow-up studies [17,18,231,256]. Results show that the weight-lowering effect of LIPOXmax training persists over more than 8 years.…”
Section: Effects Of Lipoxmax Training On Obesity and Associated Disor...supporting
confidence: 84%
“…Various help such as connected devices can be used, but clearly, regular outpatient consultations are the simplest and most efficient procedure to date to obtain good results in the long term [302]. In a recent study, Bughin and coworkers [231] found in 49 LIPOXmax-trained patients, randomized to conventional follow-up vs. a mobile telerehabilitation solution on a smartphone, that telerehabilitation was not superior to the usual care for improving body composition.…”
Section: How To Follow This Low-intensity Training?mentioning
confidence: 99%
“…The studies focused on obesity prevention and treatment in many diverse populations that ranged in age, socioeconomic background, and physical status (ie, pregnancy and post partum). App features included physical activity tracking [ 69 - 78 ], food tracking [ 70 , 72 - 83 ], knowledge, education, or recommendations [ 70 , 72 - 76 , 78 , 79 , 82 - 86 ], push notifications or scheduled reminders [ 74 - 76 , 78 , 79 , 81 - 84 , 86 ], weight monitoring [ 75 , 76 , 78 , 81 , 85 , 86 ], behavior demonstration [ 69 , 75 , 83 ], motivational challenges [ 69 , 75 - 78 , 83 ], goal setting [ 69 , 73 - 75 , 78 , 81 , 84 , 85 ], feedback [ 69 , 70 , 73 , 75 , 76 , 81 - 83 , 86 ], community support [ 70 , 75 , 78 , 85 ], connectivity to digital health devices [ 70 , 72 , 81 , 86 ], clinician portals [ 72 , 73 , 82 ], and access to a health coach [ 76 - 78 ...…”
Section: Resultsmentioning
confidence: 99%
“…Our findings for high levels of patient satisfaction are similar to those reported from other studies of telerehabilitation for disabilities other than visual impairment. Other types of disabilities or chronic conditions that reported high satisfaction with telerehabilitation included Parkinson disease, 20 , 21 chronic heart failure, 22 esophageal cancer, 23 chronic obstructive pulmonary disease, 24 , 25 neurorehabilitation, 26 speech therapy, 27 dysphagia, 28 obesity, 29 stroke, 30 , 31 and physical therapy following knee or hip replacement 32 34 or wheelchair use or mobility. 35 , 36 In response to the COVID-19 pandemic in 2020–2022, several studies have continued to report good patient satisfaction with telerehabilitation for various disabilities.…”
Section: Discussionmentioning
confidence: 99%